Use of visual means as a didactic tool in teaching English Grammar to students of 7th grade at Nuestra Señora del Rosario High School in Estelí, during the second semester 2016 - Ortega Miranda, Yajaira María | Ruíz Cruz, Marta Lorena | Hernández Valenzuela, Maritza del Carmen | Zelaya, Israel Ramón Zelaya Israel Ramón (Nicaragua | ESTELI UNAN-Managua, FAREM-Estelí, Nicaragua, 2017)
This study is aimed to investigate the effectiveness of the process of teaching English grammar to 7th grade students at Nuestra Señora Del Rosario High school in Estelí, during the second semester 2016 with emphasis on the use of visuals aids during the English class. A qualitative design was chosen for this research, and two data collection methods were used: interviews to get data from the students and class observations. The class observation and interviews provided useful information for the completion of this study. Among the main findings of this research are that visual means facilitate grammar learning, particularly images, a type of means that is commonly used by teachers. Additionally, it is important that teachers use different visual means during the class so as not to lose the attention of the students.
Seminario-(Licenciados en Ciencias de la Educación con mención en Inglés)-Universidad Nacional Autónoma de Nicaragua
Keywords: Enseñanza audiovisual | Enseñanza-Aprendizaje | Educación secundaria | Medios audiovisuales | Gramática inglesa | Inglés-Seminario-2017